2022
DOI: 10.1002/hep.32776
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐18 signaling promotes activation of hepatic stellate cells in mouse liver fibrosis

Abstract: Background and Aims: Nucleotide‐binding oligomerization domain‐like receptor‐family pyrin domain‐containing 3 (NLRP3) inflammasome activation has been shown to result in liver fibrosis. Mechanisms and downstream signaling remain incompletely understood. Here, we studied the role of IL‐18 in hepatic stellate cells (HSCs), and its impact on liver fibrosis. Approach and Results: We observed significantly increased serum levels of IL‐18 (128.4 pg/ml vs. 74.9 pg/ml) and IL‐18 binding protein (BP; 46.50 ng/ml vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…[62] NLRP3-induced liver fibrosis also involves IL-18, as IL-18-binding protein blocked hepatic inflammation and fibrosis in Nlrp3 gain-offunction mice, and IL-18 −/− mice exposed toward a dietary model of NASH had lower rates of hepatic fibrosis. [63] We demonstrated that inflammatory cytokines circulate in human chronic liver diseases, especially in case of liver cirrhosis, irrespective of etiology, supporting the notion that inflammation drives many features of chronic liver diseases. [64] Hepatic NLRP3 and caspase-1 expression are increased in patients with chronic hepatitis B infection [65] and in liver cirrhosis.…”
Section: Inflammasomes In Liver Inflammationsupporting
confidence: 72%
See 1 more Smart Citation
“…[62] NLRP3-induced liver fibrosis also involves IL-18, as IL-18-binding protein blocked hepatic inflammation and fibrosis in Nlrp3 gain-offunction mice, and IL-18 −/− mice exposed toward a dietary model of NASH had lower rates of hepatic fibrosis. [63] We demonstrated that inflammatory cytokines circulate in human chronic liver diseases, especially in case of liver cirrhosis, irrespective of etiology, supporting the notion that inflammation drives many features of chronic liver diseases. [64] Hepatic NLRP3 and caspase-1 expression are increased in patients with chronic hepatitis B infection [65] and in liver cirrhosis.…”
Section: Inflammasomes In Liver Inflammationsupporting
confidence: 72%
“…The NLRP3 inflammasome directly triggers upregulation of fibrotic markers at both mRNA and protein levels in activated HSCs, and importantly, Nlrp3 knock-in mice exhibited liver fibrosis with an increase in alpha-smooth muscle actin and collagen production independent of inflammatory infiltration 62 . NLRP3-induced liver fibrosis also involves IL-18, as IL-18-binding protein blocked hepatic inflammation and fibrosis in Nlrp3 gain-of-function mice, and IL-18 −/− mice exposed toward a dietary model of NASH had lower rates of hepatic fibrosis 63 . We demonstrated that inflammatory cytokines circulate in human chronic liver diseases, especially in case of liver cirrhosis, irrespective of etiology, supporting the notion that inflammation drives many features of chronic liver diseases 64 .…”
Section: Concepts Of Inflammation In Chronic Liver Diseasesmentioning
confidence: 98%
“…Previous studies have shown that IL-6 activates HSCs by inducing the activation of the STAT3 pathway [ 42 ]. In addition, a recent study confirmed that IL-18 can directly promote the activation of hepatic stellate cells in mouse liver fibrosis [ 43 ]. Together with TGF-β1, they mediate the activation of HSCs through different mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…The identification of IL‐1 independent mechanisms in the pathophysiology of murine CAPS directed our attention to other pro‐inflammatory cytokines, beginning with IL‐18, another inflammasome‐associated cytokine requiring caspase 1 for cleavage and activation. Mutant mice treated with an IL‐18 binding protein demonstrated significant improvement in rash, weight gain, survival, and liver pathology 141 . Similarly, mutant Nlrp3 mice on an IL‐18 or IL‐18R deficient background revealed a strong phenotypic rescue in pups with complete resolution of rash, and normal growth and survival through the first 2 months of life in the MWS model.…”
Section: Conservation Of Nlrp3 Across Speciesmentioning
confidence: 89%